2011
DOI: 10.1111/j.1532-950x.2011.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Antebrachiocarpal Ligaments in the Prevention of Hyperextension of the Antebrachiocarpal Joint

Abstract: Magnusson L-E, Ekman S: Osteoarthrosis of the antebrachiocarpal joint of 7 riding horses. Acta vet. scand. 2001, 42, 429-434.-Osteoarthrosis (OA) of the antebra-chiocarpal joint from 7 riding horses is described. The horses were old mares and developed severe OA, with ankylosis in some of the joints. The lesions were bilateral, and the owners noticed the lameness in a late event. The cause of severe OA in these mares is not clear. The fact that OA was bilateral indicates that a single traumatic injury is unlik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 11 publications
0
24
0
2
Order By: Relevance
“…The role of the palmar antebrachiocarpal stabilizers, as it has been discussed in the current literature, remains unclear. One study reported alterations in carpal extension after transection of both the palmar antebrachiocarpal ligaments, with similar effects produced by medial and lateral collateral ligament transection . Another subjective report proposed a predominant role of the PUL in limiting dorsal and palmar drawer of the manus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of the palmar antebrachiocarpal stabilizers, as it has been discussed in the current literature, remains unclear. One study reported alterations in carpal extension after transection of both the palmar antebrachiocarpal ligaments, with similar effects produced by medial and lateral collateral ligament transection . Another subjective report proposed a predominant role of the PUL in limiting dorsal and palmar drawer of the manus .…”
Section: Discussionmentioning
confidence: 99%
“…The wide standard deviation in grouped load measurements for each ligament transection condition indicate interspecimen variation in load. As such, this measurement was used to determine whether ligament transection was associated with an effect on load . The viscoelastic phenomenon of mechanical creep was evident when forces imparted by the limb to the baseplate of the jig were measured, in that these forces gradually but continuously decreased during the time that the limbs were maintained in position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We elected to remove the variability associated with the elbow angle and motion by loading the ulna directly. Another possibility of loading the antebrachium would have been to embed the proximal radius and ulna in acrylic, as previously reported . However, we intended to preserve pronation and supination.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, carpal angle was maintained at 190° ± 5° during testing. In one study, transection of the lateral collateral ligaments resulted in hyperextension of approximately 2° compared to the intact carpus . Ulnectomy with styloid excision essentially results in excision of the lateral collateral ligaments of the carpus and thus is also likely to cause slight hyperextension of the carpus.…”
Section: Discussionmentioning
confidence: 99%